Pemanfaatan Sistem Pakar untuk Mendiagnosis Penyakit pada Burung Murai Batu - Ilyas Shiddiq Pratama; Iskandar Zulkarnaen; Audy Sukma Putera; Betha Nurina Sari (Paradigma - Jurnal Komputer dan Informatika, 2022)
The stone magpie has many enthusiasts among the community and breeders, but the disease suffered by the stone magpie is a serious problem. There are various diseases that attack and cause farmers to be unable to diagnose and difficult to know the type of disease, because knowledge about these diseases is still limited in diagnosing diseases that attack stone magpies. To diagnose the type of disease, you can use this method, you can find out the symptoms of the disease, then you can determine the diagnosis of the disease and take early prevention so that the disease does not spread. Therefore, we need a system that is able to diagnose the type of disease, so that breeders or the public can find out early on the types of diseases that will attack new magpies and anticipate transmission to other animals. The results of making this expert system will display symptoms that occur, diagnosis, and prevention so that they are not contagious, which can help breeders and the public to obtain information on types of diseases and be able to assist in maintaining the health of stone magpies.